(untitled) (Journal of Parents and Teachers, 1995)
A hurried stranger seeks to fill vessels with water from the pool of dreams to help his people. Despite the heavy burden, their effort is motivated by a noble purpose. In the end, both men return with water, but only one finds satisfaction in his accomplishment.